IDEOLOGY OF MABARUNG (COMPETITION) OF PERFORMING ART IN BULELENG REGENCY - Chaya, I Nyoman (E-Journal of Cultural Studies; Volume 7, Number 1, February 2014)
Mabarung (competition) of performing art is a cultural heritage in North Bali and has highly contributed to the development of the Balinese art and culture. The tradition of mabarung of performing art which was created in Buleleng Regency constitutes the competitive arena of life in which every pebarung (the player who is involved) does his best to perform the best by optimally presenting the quality of his performance. Based on what was described above, it was necessary to reveal the tradition of mabarung of performing art in Buleleng Regency. The present study focused on the meaningfulness of the implied ideology of the mabarung of performing art in Buleleng Regency.  The result of the study showed that the cultural representation, which was actualized into the mabarung of performing art appeared from the ideas of the grass- root. The government interfered in the mabarung of performing art and a change took place; the mabarung of performing art which used to be freely performed was then performed as a festival/competition, causing the ideology it contained to change. The phenomenon of the mabarung of performing art reflected a self image; the players felt embarrassed if they lost ‘majengah-jengahan’, performed differently from others, and felt too proud of themselves ‘ajum’. In relation to that, it could be identified that the cultural representation which created the tradition of mabarung of performing art in Buleleng Regency was inspired by the ideology of freedom and self existence.
Keywords: mabarung, performing art, ideology.